1998
DOI: 10.1023/a:1025742119977
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-face confrontation: Effects of closed-circuit technology on children's eyewitness testimony and jurors' decisions.

Abstract: The present study was designed to examine effects of closed-circuit technology on children's testimony and jurors' perceptions of child witnesses. For the study, a series of elaborately staged mock trials )Vas held. First, 5to (ryear-ald and 8to 9-year-old children individually pal1icipated in a play session with an unfamiliar male confederate. Approximately 2 weeks late); children individually testified about the event at a downtown city courtroom. Mock juries composed of community recruits viewed the lrials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
176
2
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(199 citation statements)
references
References 37 publications
16
176
2
5
Order By: Relevance
“…The fact that the children in the present study averted their gaze from the questioner less during video link interactions suggests that they too were less intimidated. It is yet to be established whether the gazing behavior of child witnesses, either in open court or across LVLs, influences how credible jurors perceive them to be, an extremely important issue for the court process (Goodman et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the children in the present study averted their gaze from the questioner less during video link interactions suggests that they too were less intimidated. It is yet to be established whether the gazing behavior of child witnesses, either in open court or across LVLs, influences how credible jurors perceive them to be, an extremely important issue for the court process (Goodman et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Asch (1958) mostrou como seus participantes facilmente entravam em consenso com um grupo de confederados. Um exemplo de estudo sobre testemunhas oculares utilizando confederados incluiu um homem desconhecido em uma interação com uma criança (Goodman et al, 1998).…”
Section: Influência Social E Conformidade No Relato De Testemunhasunclassified
“…In one study, negotiating dyads who believed they were physically distant from each other achieved better agreements than did dyads who believed they were physically close (Henderson, 2011). In another study, children questioned by a remote rather than physically-present adult reported equivalent amounts of correct information, but fewer incorrect details (Doherty-Sneddon & McAuley, 2000; see also Goodman et al, 1998). The authors suggested that videomediation increased the children's confidence and made them feel less intimidated.…”
Section: Videoconferencing With Witnessesmentioning
confidence: 99%